Impacts of Chemical Reaction and Suction/Injection on the Mixed Convective Williamson Fluid past a Penetrable Porous Wedge - Hussain, Majid; Ali, Akhtar; İnç, Mustafa; Sene, Ndolane; Hussan, Muhammad (Wiley, 2022)
The impacts of chemical reaction and suction/injection in Williamson fluid flow along a porous stretching wedge are discussed in the present paper. Recently, a lot of numerical and theoretical studies are accessible for illustrating the chemical reaction impact on non-Newtonian fluids with different geometries and conditions. Considering this fact, we inspect the heat transport behavior of Williamson fluid due to a stretching porous wedge with suction or injection. The governing PDEs are converted into ODEs with reliable similarity transformation. These ODEs are solved numerically by BVP4C based in MATLAB system, and the assessment of outcomes for the validation tenacity is presented in Table. Combined plots are sketched to discern the impact of dominant sundry parameters on the flow fields. Along with them, the Sherwood number, skin friction factor, and the rate of heat transfer are also bestowed in graphs.
Keywords: Flow; Suction; Thermophoresis; Temperature; Regime